Long Non-Coding RNA MNX1-AS1 Promotes Progression of Triple Negative Breast Cancer by Enhancing Phosphorylation of Stat3 - Li, Junhua; Li, Qingjian; Li, Danhua; Shen, Zhiwen; Zhang, Kun; Bi, Zhuofei; Li, Yujuan (Frontiers in Oncology, 2020)
Abstract Triple negative breast cancer (TNBC) accounts for less than a quarter of breast cancer but has the poorest survival outcome and is prone to relapse as well as metastasis due to its aggressiveness and lack of therapeutic target. Herein, we analyzed the TCGA datasets of lncRNA expressional profiles of breast cancer vs normal tissue and TNBC vs Non-TNBC subtypes and screened a long non-coding RNA (lncRNA) MNX1-AS1 overexpressing in TNBC. We found that MNX1-AS1 were upregulated in TNBC tumor tissues and correlated with poor survival outcome in TNBC patients. Silencing MNX1-AS1 reduced the aggressiveness of TNBC in vitro and in vivo. By using RNA pulldown assay followed by western blotting and RNA immunoprecipitation (RIP), we identified Stat3 was the MNX1-AS1 binding protein and MNX1-AS1 upregulated the phosphorylation of Stat3. These studies suggested that targeting MNX1-AS1 may represent a promising therapeutic strategy to TNBC.